Pengenalan Jenis Kupu-kupu pada Murid SD 129 INPRES Kecamatan Bantimurung, Kabupaten Maros Sulawesi Selatan - Sri Nur Aminah Ngatimin; Tamrin Abdullah; Andi Nasruddin; Ahdin Gassa (Jurnal Hutan dan Masyarakat, 2017)
The aim of research is to identification butterflies species at Pattunuang Resort and increased knowledge of Elementary School students about the roles of insects as pollinators and main part of biodiversity in nature. The research as a survey was conducted in Pattunuang Resort and SDN 129 Inpres Bantimurung Regency, Maros District from March to May 2017. The steps of research was:  1) build transect lines for butterflies observation; 2) butterfly identification and counting of their population used Shannon-Wiener Index Biodiversity, then 3) introducing butterflies species to Elementary School students Class Five at SDN 129 Inpres Bantimurung. The result was showed, we find  20 individual butterflies from 6 species of Papilionids (Troides haliphron, T. helena, Papilio demoleus, P. demolion and Graphium agamemnon), also Danaus chrysippus from Nymphalids. Based value of Shannon-Wiener Index, we find very low criteria of butterflies (H < 1). The conclusion : 1) findings of 20 butterflies individual from 6 species (Papilionids and Nymphalids); 2) approximately  57.3% of Elementary School students recognized butterflies species and 3) 28.8% from them as a butterflies wild hunter. Recommendation for the future, we need more collaborative research and development from University and local government increasing introducing butterflies conservation species for Elementary School students around Pattunuang Resort.